The development of rainfall temporal pattern in Klang Valley - Afiqah Fairuz, Mahmud (2017)
The design rainfall is vital in engineering practice as a part of sustainable water resources management. Rainfall temporal pattern is needed in studies related to water resources. This study would assist more reliable rainfall data that is required which will be later converted into the corresponding design stream flow event. In addition to this, a design rainfall event needed rainfall duration, average rainfall intensity of an Average Recurrence Interval (ARI) and rainfall temporal pattern. In Malaysia, design flood estimation are widely used with different method. A study on temporal pattern is important for flood estimation as well as runoff computation, and further influence the water resource management and planning. Rainfall temporal pattern is design based on the intensity and diversity of rainfall. Both factors are needed to produce a set of rainfall temporal pattern. This study focused on the area of Klang Valley where 14 rainfall stations are allocated in that area. The data of 5 minutes rainfall for 17 years starting from 2000 to 2016 are collected from Department of Irrigation and Drainage (DID), Malaysia and were analysed to develop the rainfall temporal pattern for this area. However, this study only covered a part of Klang Valley, which involved only Wilayah Persekutuan Kuala Lumpur, Gombak, Hulu Langat, Klang and Petaling Jaya. The proposed method using Average Variability Method (AVM) is recommended in Malaysian Urban Storm Water Management (MSMA) meanwhile Huff Time Distribution Method (HTDM) is used to simplify analyses and presentation. The developed temporal rainfall pattern involved with 15 minutes, 30 minutes, 60 minutes and 180 minutes for AVM. Meanwhile HTDM involved with 60 minutes, 120 minutes and 180 minutes only. As the different of percentage less than 100% for 30 minutes duration, 60 minutes duration and 180 minutes it shows that the pattern of temporal can be form properly.